2022
DOI: 10.3390/ijerph19148333
|View full text |Cite
|
Sign up to set email alerts
|

National Implementation of a Group-Based Program Promoting Patient Engagement and Peer Support in the Veterans Health Administration: A Multi-Methods Evaluation

Abstract: Evidence-based approaches promoting patient engagement and chronic illness self-management include peer support, shared decision-making, and education. Designed based on these components, Taking Charge of My Life and Health (TCMLH) is a group-based, ‘Whole Person’ care program promoting mental and physical self-care and patient empowerment. Despite evidence of effectiveness, little is known about implementation for TCMLH and similar programs. In this first-of-its-kind, multi-methods evaluation conducted betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Identification of impactful program elements may be applied to solidifying program fidelity criteria especially given the desire for modified formats ( 21 , 33 , 89 ). This study can be applied to planning future research on program outcomes, including development of measures for various types of outcomes that occur during the process of behavior change, including the different types of self-efficacy, social identification, and empowerment, in addition to outcomes in physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of impactful program elements may be applied to solidifying program fidelity criteria especially given the desire for modified formats ( 21 , 33 , 89 ). This study can be applied to planning future research on program outcomes, including development of measures for various types of outcomes that occur during the process of behavior change, including the different types of self-efficacy, social identification, and empowerment, in addition to outcomes in physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Our multi-component evaluation of TCMLH was part of a larger project to design, implement, and evaluate Whole Health educational and wellness programming throughout the VHA system from 2013 to 2020 (VA777-12-C-002; Rychener, PI). We evaluated the TCMLH program from 2016 to 2018, assessing facilitator trainings ( 21 ), site implementation ( 33 ), and participant outcomes ( 34 , 35 ). Our studies of veteran participant outcomes after attending TCMLH found significant improvements from baseline to program conclusion in outcomes related to patient self-management (patient activation, patient motivation, and self-care behaviors) and health indicators (global mental health, perceived stress, and quality of life) ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding these veterans’ obstacles would inform strategies for engaging veterans in health services. For example, peer support services may encourage veterans who perceive internal barriers to seek help (Drake et al, 2022). As such, additional research is warranted to inform efforts to engage veterans in programs to mitigate adverse outcomes of veterans experiencing homelessness and criminal legal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…CSP has driven the development of multiple new trainings in its 10-year existence, using input from the eld staff. For example, trainings on intimate partner violence, peer support programs, and trainings that address caregiving challenges for speci c diseases have been developed, disseminated, and re ned [17,18]. And yet, even in the VA Health Care System, around 50% of caregivers report they have not received the training they need [19].…”
Section: Introductionmentioning
confidence: 99%